Pericytes and vascular smooth muscle cells in central nervous system arteriovenous malformations - Nakisli, Sera; Lagares, Alfonso; Nielsen, Corinne M.; Cuervo, Henar (Frontiers in Physiology, 2023)
Previously considered passive support cells, mural cells—pericytes and vascular smooth muscle cells—have started to garner more attention in disease research, as more subclassifications, based on morphology, gene expression, and function, have been discovered. Central nervous system (CNS) arteriovenous malformations (AVMs) represent a neurovascular disorder in which mural cells have been shown to be affected, both in animal models and in human patients. To study consequences to mural cells in the context of AVMs, various animal models have been developed to mimic and predict human AVM pathologies. A key takeaway from recently published work is that AVMs and mural cells are heterogeneous in their molecular, cellular, and functional characteristics. In this review, we summarize the observed perturbations to mural cells in human CNS AVM samples and CNS AVM animal models, and we discuss various potential mechanisms relating mural cell pathologies to AVMs.